Microaerophilic growth characteristics of Pseudomonas aeruginosa importance to the successful treatment of chronic infections in cystic fibrosis lungs - Vaz, Raquel Alexandra Palas (2016)
Patients with CF lung disease are susceptible to chronic infections by various pathogens, such as Pseudomonas aeruginosa. This pathogen is able to adaptat to the environment in CF lungs, characterized by inflammatory defences, oxygen restriction, and poor nutrient availability. It is well established that, once P. aeruginosa infection is installed in the lungs, it is almost impossible to eradicate, due to sophisticated genotypic and phenotypic adaptation mechanisms that develop according to the stage of infection. Understanding those changes and the identification of specific characteristics that allow P. aeruginosa eradication before the onset of chronic infection is urgent. In this work, P. aeruginosa adaptation under microaerophilic and anaerobic conditions was assessed in terms of phenotypic charatceristics, antibiotic susceptibility and expression of antibiotic resistance mechanisms (mexAB operon). Results showed, when compared with aerobic conditions, similar growth and emergence of intermediate resistance profiles for ciprofloxacin and imipenem, but no significant variation in operon mexAB expression. It was also observed an increase of colony morphotypes with the decrease of oxygen availability, mainly in 5% O2. Nevertheless oxygen depletion has no significant effect on P. aeruginosa growth and mexAB expression, affecting, however, the phenotypic characteristics and antibiotic susceptibility profiles. Despite the overall observations, the microaerophilic environment with 5% O2, seems to demonstrate a transient distinct behaviourwhich can be a point of evolution into chronic infection and as such a possible treatment target.